﻿Integrating multimodal literacies in ESL teaching: addressing learner diversity - ﻿Gurnam Kaur Sidhu ,; ﻿Sarjit Kaur , (Universiti Kebangsaan Malaysia, 2009)

(untitled)
﻿In today's technologically-dependent globalised era, the "performance chasm" among diverse ESL learners is a topic for discussion by educators, policymakers and concerned citizens in many communities in the developing world. These concerns make it necessary for ESL teachers to use effective teaching strategies that not only to enhance English language proficiency but also to determine the elements of student diversity in their ESL classrooms. It is widely recognised that English literacy is interwoven into the fabric of rapid development of new technologies and cannot be separated from our everyday lives. Hence, this article presents a case study using the multiliteracies approach that accommodates the broad repertoire of textual practices and multimodal literacies in a language classroom. This study found that students are actively involved in the process of learning through the multiple modes of meaning making within the scope of their task-based project. As such, the multimodal aspects of this case study allow contextualised meanings to be created by the students through the use of multiple semiotic resources and media. More importantly, the multiliteracies approach has managed to help the participants to address learner diversity in a more integrated and contextualised manner.